1999
DOI: 10.1097/00007890-199911150-00022
|View full text |Cite
|
Sign up to set email alerts
|

ANTI-CD154 OR CTLA4Ig OBVIATES THE NEED FOR THYMIC IRRADIATION IN A NON-MYELOABLATIVE CONDITIONING REGIMEN FOR THE INDUCTION OF MIXED HEMATOPOIETIC CHIMERISM AND TOLERANCE1

Abstract: One injection of anti-CD154 or CTLA4Ig overcomes the need for TI or prolonged host TCD in a preclinical model for the induction of mixed chimerism and deletional tolerance and thus further decreases the toxicity of this protocol. Achievement of tolerance with conditioning given over 24 hr suggests applicability to cadaveric organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 42 publications
2
70
0
1
Order By: Relevance
“…The two long-term chimeras that were prepared with 3 Gy TBI and MR1 alone also showed donor-specific unresponsiveness in MLR and CML, as well as marrow, spleen, and thymic chimerism at the time of sacrifice (34 wk) (data not shown). Thus, lasting chimerism and systemic donor-specific tolerance was reliably induced across a full MHC barrier in chimeras prepared with an incompletely depleting dose of TCD plus MR1, similar to results seen in other mixed chimeras (10). Although similar results were obtained in a minority of mice receiving MR1 without TCD mAbs, MR1 alone did not reliably allow this outcome to be achieved.…”
Section: Incompletely Depleting Doses Of Anti-cd4 and Anti-cd8 Mabs Osupporting
confidence: 66%
See 3 more Smart Citations
“…The two long-term chimeras that were prepared with 3 Gy TBI and MR1 alone also showed donor-specific unresponsiveness in MLR and CML, as well as marrow, spleen, and thymic chimerism at the time of sacrifice (34 wk) (data not shown). Thus, lasting chimerism and systemic donor-specific tolerance was reliably induced across a full MHC barrier in chimeras prepared with an incompletely depleting dose of TCD plus MR1, similar to results seen in other mixed chimeras (10). Although similar results were obtained in a minority of mice receiving MR1 without TCD mAbs, MR1 alone did not reliably allow this outcome to be achieved.…”
Section: Incompletely Depleting Doses Of Anti-cd4 and Anti-cd8 Mabs Osupporting
confidence: 66%
“…In previous studies, we showed that costimulatory blockade with one injection of anti-CD40L or of CTLA4Ig obviates the need for thymic irradiation or repeated administration of TCD mAbs to overcome intrathymic alloresistance in mice receiving one injection of depleting anti-CD4 and anti-CD8 mAbs (10). The current demonstration that anti-CD4 mAb is not required to achieve such results (i.e., that anti-CD40L and anti-CD8 mAb alone are sufficient to allow the reliable induction of durable mixed chimerism and transplantation tolerance) is of considerable clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, relatively little is known of factors that control B cell responses following allograft tolerance induction. Indeed, most investigations of the induction of allograft tolerance have focused on the regulation of T cell responses (1)(2)(3)(4). We hypothesize that control of B cell responses is necessary for stable long-term allograft survival.…”
mentioning
confidence: 99%